Analysis of The Probability of Money Laundering Crimes toward the Development of Crypto-currency Regulations in Indonesia - Muttaqim, Muttaqim; Apriliani, Desi (Universitas Negeri Semarang (UNNES), 2019)
Cryptocurrency is done instantly, so it does not require a third party (the central bank as the holder of moneter policy). All transactions in the Cryptocurrency system will be collectively verified in a private network. Today Cryptocurrency transaction activities are prohibited in Indonesia in line with the issuance of Bank Indonesia Regulation number 18 of 2016 concerning the Implementation of Payment Transaction Processing. Taking into account that the clarity of the Cryptocurrency system is not very good and is still in the government assessment stage even though it is noted that the exchange rate of virtual currencies is very high, in 2017 the price of one Bitcoin is closed equivalent to 4,224 US dollars or around Rp. 56,000,000, with market capitalization (Marketcap) for 71.5 billion US dollars, equivalent to Rp. 954 trillion which makes investors choose to challenge inventories on Cryptocurrency or digital currency rather than investing in safe havens such as gold or bonds. This study will discuss how Cryptocurrency can provide potential money laundering criminal offenses in the form of digital transaction systems and how the regulations are developed. Given the legal conditions for proving money laundering crimes originating from criminal acts of corruption often find it difficult, especially against Cryptocurrency as a currency that is not recognized in Indonesia and the peer-to-peer nature that increasingly makes Cryptocurrency very private and difficult to trace.